Effects of a Self-Oral Health Care Program and Oral Mucositis Symptoms in Cancer Patients Receiving Chemotherapy - Narksanong, Sairudee (Health Science Clinical Research, 2022)
Abstract Objective: To compare the symptoms of mucositis among cancer patients receiving chemotherapy among those receiving the oral care program. and groups receiving normal care Methods: This is an intervention research clustered non-randomized design study in cancer patients treated with chemotherapy aged 20-80 years and over at the chemotherapy unit. Uttaradit Hospital consisted of 96 people. The experimental group consisted of 48 patients receiving chemotherapy Monday, Wednesday and Friday using the oral care program, while the control group consisted of Tuesday and Thursday chemotherapy patients. It was the same group of 48 people receiving normal care. Records of first-day oral condition of patients on day 7 and 14. Comparative analysis of the incidence and severity of stomatitis between the 2 groups using t-test and exact probability test and adjusted. Difference of preliminary characteristics by multivariable logistic regression statistics, frequency of satisfaction analysis, percentage Results: When comparing the results of the oral care program between the experimental group and the control group. It was found that the incidence of mucositis and the degree of severity statistically significant difference Self-care program was shown to reduce the incidence of mucositis (p=0.070) and significantly reduce the severity of mucositis (p=0.001). Conclusion: The continued use of oral care programs in clinical practice should be encouraged. Keywords: oral mucositis, Orem’s self-care theory, oral care program, cancer patient, chemotherapy